Optimum paste temperature for oil extraction using IAR motorised kneader - Gyuse, E. T.; Yiljep, Y. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
An experiment to determine optimum paste temperature for oil extraction using the Institute for Agricultural Research (IAR) motorised kneader was conducted at the Agricultural Engineering Department of Ahmadu Bello University Zaria, in 2002. Some 20 kg of groundnut paste from the Manipinta variety (locally known as Kampala) with 55% oil content at 5 - 6% moisture content was used for the experiment. The paste was divided into five equal replicates (of 4kg each) for use with motorised kneader. Results show that IAR motorized kneader enhanced extraction efficiency at low values of paste temperatures. Optimum extraction efficiencies of 88.31 – 98.55% were obtained at paste temperature of 23.50 – 25.00oC, corresponding to atmospheric and added water temperatures of between 15.75 – 23.09 and 22.00 – 26.00oC, respectively. It is therefore recommended that groundnut paste at elevated temperature be allowed to cool to about 24.50oC before kneading. The optimum extraction efficiency of the kneader was realized at room temperature during the harmattan season.